Social Media Marketing and Product Quality on Purchase Intention of All-You-Can-Eat Restaurant - Surianto, Surianto; Yulita, Henilia; Wijaya, Brendi; Ibrahim, Audi Arief (Politeknik Piksi Ganesha Indonesia, 2024)
Social media marketing is a technique for someone to carry out marketing activities through social media or word of mouth, by promoting products to potential consumers in online platform. Pempek-Yuk Restaurant! is the first restaurant to provide culinary with the